Case report: Cervical brachytherapy technique for locally advanced cervical cancer in a patient with complete bicorporeal uterus - Ding, Lipeng; Zheng, Zhangcai; Cao, Yueao; Wang, Zhenjiang; Zhu, Baoyu; Miao, Guoying; Yuan, Wenzhen (Frontiers in Oncology, 2024)
Purpose: To describe an approach to cervical brachytherapy for a patient with a complete bicorporeal uterus and locally advanced cervical cancer (LACC).The patient was a 53-year-old woman with a complete bicorporeal uterus, diagnosed with stage IIB cervical squamous cell carcinoma due to contact bleeding. The patient underwent concurrent chemoradiotherapy (CCRT), external beam pelvic radiotherapy with 45Gy/25 fractions, and weekly cisplatin (40 mg/m2). Brachytherapy was administered following the completion of external beam radiotherapy.The brachytherapy, which was CT-guided using two CT-compatible tandems and two CT-compatible ovoids, delivered a prescription dose of HRCTV D90 was 6Gy*5F, which achieved satisfactory dose coverage. The patient's final HRCTV D90 EQD210 was 84.9Gy, and IRCTV D90 EQD210 was 63.5Gy. Rectum D2cc EQD23 was 66.03Gy, bladder D2cc EQD23 was 75.57Gy, sigmoid D2cc EQD23 was 63.93Gy, and intestine D2cc EQD23 was 65.86Gy.Follow-up at 1 year was CR.For patients with cervical cancer and a complete bicorporeal uterus, using double tandems combined with double ovoids is a feasible treatment method to ensure adequate dose coverage without causing additional damage. This method is also applicable to patients with endometrial cancer.